Trial to assess the tolerability of using felodipine to upregulate autophagy as a treatment of Huntington’s disease (FELL-HD): a phase II, single-centre, open-label, dose-finding trial protocol - Roger A Barker; Laura Oakley; Emma Cutting; David C Rubinsztein; Dimitrios Apostolopoulos; Nikolaos Demiris; Katie Andresen; Amy H Evans; Alimu Dayimu; Katherine Bongaerts; Robyn Staples; Wendy Gooding (BMJ Open)
Introduction Huntington’s disease (HD) is an autosomal dominant neurodegenerative disorder that presents with a progressive movement disorder along with cognitive and psychiatric problems. It is caused by a Cytosine-adenin-guanine (CAG) expansion in exon 1 of the huntingtin gene which codes for mutant huntingtin (mHTT) that over time accumulates in cells, causing dysfunction and then death through new toxic gain-of-function mechanisms. Autophagy has been shown to be critical for the degradation of diverse intracytoplasmic aggregate-prone proteins that cause neurodegenerative disease, including mHTT. From a screen of a library enriched in approved drugs, felodipine was selected as the most suitable candidate showing strong autophagy-inducing effects in preclinical models of HD. We are, therefore, conducting a trial to assess the safety and tolerability of felodipine in people with early HD.Methods and analysis FELL-HD is a phase II, single-centre, open-label, dose-finding trial in people with early HD. 18 participants with early clinical features of the disease will be treated with felodipine for 58 weeks, with a further 4-week follow-up. The primary outcome measure is the number of adverse events attributable to felodipine. Exploratory outcomes include additional measures of motor and cognitive function, non-motor symptoms and quality of life scales, as well as peripheral and central disease biomarkers assessed through brain MRI. Analysis of blood and cerebrospinal fluid will also be performed through an associated sample study, FELL HD-s.Ethics and dissemination The study was approved by the London-Brent Research Ethics Committee (reference 22/LO/0387) and has been accepted by the Medicines and Healthcare products Regulatory Agency for clinical trials authorisation (reference CTA 12854/0256/001-0001). A lay summary of the results of the trial will be uploaded to our research group website which is publicly accessible. A webinar or in-person open day, to present results of the trial to participants and our wider cohort of patients who attend our centre, will be held once the trial is completed. The results of the trial will also be published in scientific journals and presented at national and international conferences.Trial registration numbers EudraCT-2021-000897-27, ISRCTN56240656.